#### Answer

=($x^{2}$+3)($x^{2}$+2)

#### Work Step by Step

$x^{4}$+5$x^{2}$+6=
=$x^{4}$+2$x^{2}$+3$x^{2}$+6=
=$x^{2}$($x^{2}$+2)+3($x^{2}$+2)=
=($x^{2}$+3)($x^{2}$+2)

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

=($x^{2}$+3)($x^{2}$+2)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.